Outcomes On Psycholosocial Factors And Nutrition-Related Quality Of Life: Evaluation Of A 10-Week Nutrition Education Intervention In University Students - Mohd Razif, Shahril; Pei Lin, Lua; Wan Putri Elena, Wan Dali (2014)
The purpose of this study was to evaluate the effectiveness of nutrition education intervention among university students in terms of social, psychological factors and nutrition-related Quality of Life (NQoL) outcomes after receiving a 10-week nutrition education. Longitudinal and randomised study design was adopted for the study. Methods: A total of 417 respondents from four public universities in Terengganu were randomly assigned to either intervention group (IG = 205) or control group (CG = 212). The IG received nutrition education through three tools; 1) conventional lecture, 2) brochures and 3) text messages via short messaging system (SMS) while the CG not received any intervention. Students completed the Malay version of NQoL (6 domains; 49 items; Likert-type responses=1-5) and SF-36 (8 domains; 36 items) at pre-intervention and post-intervention. Data analysis was carried out by using SPSS 16.0 utilising descriptive and parametric statistics. Results: Ninety-one percent of participants (IG = 178; CG = 202) completed the study (age = 19.1±1.1 years; female = 87.6%; Malay = 98.2%). After controlling for possible confounders (eg. weight, waist, hip circumferences and pre-intervention scores for each domain), IG possessed relatively higher NQoL score in Food Impact (p = 0.001), Social / Interpersonal (p = 0.008), Physical Functioning (p = 0.011) and Overall NQoL (p = 0.001). However, Psychological Factors did not show any significant difference for both groups. Conclusion: Although the intervention did not generate significant impact in the psychological component over a period of 10 weeks, significant positive impacts in Social/Interpersonal aspects and NQoL were clearly shown. ASEAN Journal of Psychiatry, Vol. 15 (1): January – June 2014: 39-53.